2006
DOI: 10.4049/jimmunol.177.6.4211
|View full text |Cite
|
Sign up to set email alerts
|

Mannose-Binding Lectin Contributes to the Severity of Guillain-Barré Syndrome

Abstract: In Guillain-Barré syndrome (GBS), complement activation plays a crucial role in the induction and extent of the postinfectious immune-mediated peripheral nerve damage. Mannose-binding lectin (MBL) activates the complement system via the lectin pathway after recognition of repetitive sugar groups on pathogens. We investigated whether the MBL2 genotype, serum MBL level, and MBL complex activity are associated with the development and severity of GBS. Single nucleotide polymorphisms in the promoter region (−550 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 49 publications
3
19
0
Order By: Relevance
“…In the present study nonsignificant differences for the frequencies of MBL2 haplotypes and genotypes were observed between ICU patients with SIRS and healthy controls. The prevalence of low-MBL2 genotypes was similar to the frequency observed by Garcia-Laorden et al in Spain (10) and others in previous studies (17,18). LYPB, as previously reported in other Caucasian populations (1,46), was the predominant variant type of haplotype both in the group of patients with SIRS and in the healthy blood donors.…”
Section: Discussionsupporting
confidence: 71%
“…In the present study nonsignificant differences for the frequencies of MBL2 haplotypes and genotypes were observed between ICU patients with SIRS and healthy controls. The prevalence of low-MBL2 genotypes was similar to the frequency observed by Garcia-Laorden et al in Spain (10) and others in previous studies (17,18). LYPB, as previously reported in other Caucasian populations (1,46), was the predominant variant type of haplotype both in the group of patients with SIRS and in the healthy blood donors.…”
Section: Discussionsupporting
confidence: 71%
“…Genetically defined MBL deficiency is remarkably common in the general population, with an estimated prevalence of more than 10 to 15% in several Caucasian populations (17,18). In our study, the MBL2 genotype frequencies observed in the healthy control group closely resembled those previously reported in a Canary Islands (Spain) population (9), which in turn was similar to that observed in other healthy control groups from several European studies performed with Caucasian populations (1,12,13). LYPB, as previously reported, was the predominant variant type haplotype both in the healthy control group and in the patients with AP.…”
Section: Discussionsupporting
confidence: 78%
“…The multivariate analysis has revealed that the presence of MBL2 genotypes associated with low MBL production was the only variable associated with septic shock even though other clinical variables, such as age, immunosuppression, and diabetes mellitus, previously related to AP with an unfavorable outcome (27,29,32,44) were also included in the study. Although one possible limitation of our study is the fact that serum MBL levels were not measured, the relationship between MBL2 genotypes and serum MBL levels has been clearly established in numerous studies (12,13,40). Therefore, MBL2 genotyping could be of clinical interest as a molecular marker defining patients with AP at risk for septic shock.…”
Section: Discussionmentioning
confidence: 99%
“…More serious conditions that can arise from C. jejuni infections include Guillain-Barré syndrome, which is the most common cause of acute flaccid paralysis in the United States [171] and Miller-Fisher syndrome. These diseases result in damage to the nerve gangliosides by antibody mediated axonal cytoskeletal breakdown and peri-synaptic Schwann cell damage.…”
Section: Elucidation Of the Pseudaminic Acid Biosynthetic Pathwaymentioning
confidence: 99%
“…The link between these neuropathies and C. jejuni is thought to come about due to the bodies' production of antibodies against C. jejuni lipopolysaccharides (in C. jejuni these are analogous to lipooligosaccharides of mucosal pathogens), which cross-react with gangliosides. It is believed that lectin-binding proteins within the immune system recognize glycan binding sites on pathogens and activate the complement system thus producing these cross-reactive antibodies [171,172]. This crossreactivity is thought in part to be due to the presence of Nacetyl neuraminic acid (Neu5Ac) (9) that is displayed in prominent positions on vertebral cells and is critical for a number of physiological processes including neuronal plasticity [173], and is also found on the oligosaccharide portion of C. jejuni cell surface proteins.…”
Section: Elucidation Of the Pseudaminic Acid Biosynthetic Pathwaymentioning
confidence: 99%